Tertiary lymphoid structures and B-cell infiltration are IPF features with functional consequences - Cocconcelli, Elisabetta; Balestro, Elisabetta; Turato, Graziella; Fiorentù, Giordano; Bazzan, Erica; Biondini, Davide; Tinè, Mariaenrica; Bernardinello, Nicol; Pezzuto, Federica; Baraldo, Simonetta; Calabrese, Fiorella; Rea, Federico; et al. (Frontiers in Immunology, 2024)
Background. Recent literature has shown the presence of B-cells and autoantibodies in IPF which would imply the presence of Tertiary Lymphoid Structures (TLS, sites where the immune response is triggered), yet TLS are not considered features of the histological characteristics of IPF.Aim. To quantify presence, size and degree of activation of TLS in biopsied and explanted-lungs from patients with early and late IPF, never treated with antifibrotics, and relate their presence and activity to the clinical course, disease progression and lung inflammation.Methods. Immunochemistry for B-cells, CD4, CD8 and CD45 cells was performed in lung tissue from IPF patients, 18 at diagnosis (early), 39 explanted (end-stage) and 12 smoking controls. TLS activation was assessed by CD40 expression. Spirometry along 31(12-72) months of follow-up was used to characterize end-stage IPF as slowprogressors or rapid-progressors.Results. B-cells along with other inflammatory cells were higher in early and end-stage IPF than in controls (p<0.001). In rapid-progressors all inflammatory cells were higher than in slow-progressors (p<0.05). TLS were present in 100% of early and end-stage IPF and in 50% of controls. In end-stage IPF, TLS area and activation-score were higher than in early IPF (p<0.0001; p=0.005) and controls (p<0.04; p<0.002). TLS activation score correlated with FVC decline during follow-up in rapid-progressors (r=0.73; p=0.007) but not in slow-progressors.A prominent B-cell infiltration along with the presence of TLS, which activity correlates with FVC-decline, are important components of IPF from the beginning of the disease, likely playing an important role on its mechanism and progression.